Effect of Segment-Body Vibration on Strength Parameters - Goebel, Ruben Tobias (Sports Med Open, 2015)
BACKGROUND: In this study, we examine the biomechanical advantage of combining localized vibrations to hamstring muscles involved in a traditional resistance training routine. METHODS: Thirty-six male and female participants with at least 2 years of experience in resistance training were recruited from the German Sport University Cologne. The participants were randomized into two training groups: vibration training group (VG) and traditional training group (TTG). Both groups underwent a 4-week training phase, where each participant worked out at 70 % of the individual 1 repeat maximum (RM—maximum load capacity of a muscle for one lift to fatigue) (4 sets with 12 repetitions each). For participants in the VG group, local vibration was additionally applied directly to hamstring muscles during exercise. A 2-week examination phase preceded the pretests. After the pretests, the subjects underwent a prescribed training for 4 weeks. At the conclusion of the training, a 2-week detraining was imposed and then the study concluded with posttests and retest. RESULTS: The measured parameters were maximum isometric force of the hamstrings and maximum range of motion and muscle tension at maximum knee angle. The study revealed a significant increase in maximum isometric force in both training groups (VG = 21 %, TTG = 14 %). However, VG groups showed an increase in their range of motion by approximately 2 %. Moreover, the muscle tension at maximum knee angle increased less in VG (approximately 35 %) compared to TG (approximately 46 %). CONCLUSIONS: We conclude that segment-body vibrations applied in resistance training can offer an effective tool to increase maximum isometric force, compared to traditional training. The cause for these findings can be attributed to the additional local vibration stimulus.